Sanksi Pelaku Tindak Pidana Kepemilikan Satwa Dilindungi dalam Putusan Nomor 809/PID.SUS/2024/PN.DPS Perspektif Hukum Pidana Islam - Ali, M. Farhan; Saepulloh, Usep; Najmudin, Deden (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study addresses the issue of sanctions against perpetrators of the crime of possession of protected wildlife, focusing on the analysis of Denpasar District Court Decision No. 809/Pid.Sus/2024/PN.Dps. The main problem in this study is the judge's legal considerations in issuing an acquittal for the defendant, as well as how Islamic criminal law examines the case. This research differs from previous studies by integrating positive criminal law and Islamic criminal law perspectives simultaneously. This study uses a normative juridical method with statutory, conceptual, analytical, and case study approaches. The results indicate that the judge considered the defendant's legal ignorance, lack of malicious intent (mens rea), and lack of outreach from relevant agencies. From an Islamic legal perspective, the defendant's actions are categorized as ta'zir crimes, for which sanctions are entirely left to the judge's discretion. This study demonstrates the importance of a substantive justice approach in environmental law enforcement that is not solely based on formal legality but also considers the social context and moral values